Racial and Socioeconomic Disparities in CKD in the Context of Universal Health Care Provided by the Military Health SystemPlain-Language Summary - Jenna M. Norton; Lindsay Grunwald; Amanda Banaag; Cara Olsen; Andrew S. Narva; Eric Marks; Tracey P. Koehlmoos (Kidney Medicine, 2022)
Rationale & Objective: Health-impeding social determinants of health—including reduced access to care—contribute to racial and socioeconomic disparities in chronic kidney disease (CKD). The Military Health System (MHS) provides an opportunity to assess a large, diverse population for CKD disparities in the context of universal health care. Study Design: Cross-sectional study. Setting & Participants: MHS beneficiaries aged 18 to 64 years receiving care between October 1, 2015, and September 30, 2018. Predictors: Race, sponsor’s rank (a proxy for socioeconomic status and social class), median household income by sponsor’s zip code, and marital status. Outcome: CKD prevalence, defined by International Classification of Diseases, Tenth Revision codes and/or a validated, laboratory value-based electronic phenotype. Analytical Approach: Multivariable logistic regression compared CKD prevalence by predictors, controlling separately for confounders (age, sex, active-duty status, sponsor’s service branch, and depression) and mediators (hypertension, diabetes, HIV, and body mass index). Results: Of 3,330,893 beneficiaries, 105,504 (3.2%) had CKD. In confounder-adjusted models, the CKD prevalence was higher in Black versus White beneficiaries (OR, 1.67; 95% CI, 1.64-1.70), but lower in single versus married beneficiaries (OR, 0.77; 95% CI, 0.76-0.79). The prevalence of CKD was increased among those with a lower military rank and among those with a lower median household income in a nearly dose-response fashion (P < 0.0001). Associations were attenuated when further adjusting for suspected mediators. Limitations: The cross-sectional design prevents causal inferences. We may have underestimated the CKD prevalence, given a lack of data for laboratory tests conducted outside the MHS and the use of a specific CKD definition. The transient nature of the MHS population may limit the accuracy of zip code–level median household income data. Conclusions: Racial and socioeconomic CKD disparities exist in the MHS despite universal health care coverage. The existence of CKD disparities by rank and median household income suggests that social risks may contribute to both racial and socioeconomic disparities despite access to universal health care coverage.